Simultaneous Analysis of Cyanotoxins β-N-methylamino-L-alanine (BMAA) and Microcystins-RR, -LR, and -YR Using Liquid Chromatography–Tandem Mass Spectrometry (LC-MS/MS) - Sercan Pravadali-Cekic; Aleksandar Vojvodic; Jake P. Violi; Simon M. Mitrovic; Kenneth J. Rodgers; David P. Bishop (Molecules, 2023)
β-N-methylamino-L-alanine (BMAA) and its isomers, 2,4-diaminobutyric acid (2,4-DAB) and N-(2-aminoethyl)-glycine (AEG), along with microcystins (MCs)-RR, -LR, and -YR (the major MC congeners), are cyanotoxins that can cause detrimental health and environmental impacts during toxic blooms. Currently, there are no reverse-phase (RP) LC-MS/MS methods for the simultaneous detection and quantification of BMAA, its isomers, and the major MCs in a single analysis; therefore, multiple analyses are required to assess the toxic load of a sample. Here, we present a newly developed and validated method for the detection and quantification of BMAA, 2,4-DAB, AEG, MC-LR, MC-RR, and MC-YR using RP LC-MS/MS. Method validation was performed, assessing linearity (r2 > 0.996), accuracy (>90% recovery for spiked samples), precision (7% relative standard deviation), and limits of detection (LODs) and quantification (LOQs) (ranging from 0.13 to 1.38 ng mL−1). The application of this combined cyanotoxin analysis on a culture of Microcystis aeruginosa resulted in the simultaneous detection of 2,4-DAB (0.249 ng mg−1 dry weight (DW)) and MC-YR (4828 ng mg−1 DW). This study provides a unified method for the quantitative analysis of BMAA, its isomers, and three MC congeners in natural environmental samples.